Islamic And Human Rights Perspectives on The Discourse on The Existence of Gender-Neutral Toilets in Indonesia: Penelitian - Kaokabah; Rabith Madah Khulaili Harsya; Aklima Aklima; Tono Wartono; Darmun (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2026)
The discourse on gender-neutral toilets has sparked a multidimensional debate in Indonesia, a Muslim-majority country that upholds religious values ​​and Eastern norms. This study aims to analyze the existence of gender-neutral toilets through a dual lens: the perspective of Islamic law (Maqasid al-Shari'ah) and international human rights instruments. Using normative legal research methods with a conceptual and comparative approach, this article explores the tension between the inclusiveness of public spaces for gender minorities and the principles of privacy ( khalwah ) and gender segregation in Islamic tradition. The results show that while the human rights perspective emphasizes non-discriminatory accessibility and human dignity according to the Yogyakarta principles, the Islamic perspective in Indonesia tends to emphasize the protection of public morality and the boundaries of aurat. However, there is a dialectical space through the principle of maslahah mursalah to provide safe facilities without disrupting the existing social order. This study concludes that the implementation of gender-neutral toilets in Indonesia requires a hybrid model that takes into account local sensitivities to avoid escalating social conflict.